Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/batteries5010030
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Index Measurement of Lithium Ion Battery Electrolyte with Etched Surface Cladding Waveguide Bragg Gratings and Cell Electrode State Monitoring by Optical Strain Sensors

Abstract: In this scientific publication, a new sensor approach for status monitoring, such as state of charge and state of health, of lithium ion batteries by using special Bragg gratings inscribed into standard optical glass fibers is presented. In addition to well-known core gratings, embedded into the anode of 5 Ah lithium ion pouch cells as a strain monitoring unit, the manufacturing of a surface cladding waveguide Bragg grating sensor incorporated into the cell’s separator, that is sensitive to changes of the refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…It is shown that FBGs exhibit 28 % lower rise time compared to K-Type thermocouples, emphasizing their real-time monitoring capabilities [355]. Furthermore, it is suggested that FBGs are deployable within the jelly roll or even in the electrode coatings [336,[356][357][358][359]. The mechanical and temperature changes during operation can be precisely monitored in this position.…”
Section: Mechanical and Volumetric Change Detectionmentioning
confidence: 99%
“…It is shown that FBGs exhibit 28 % lower rise time compared to K-Type thermocouples, emphasizing their real-time monitoring capabilities [355]. Furthermore, it is suggested that FBGs are deployable within the jelly roll or even in the electrode coatings [336,[356][357][358][359]. The mechanical and temperature changes during operation can be precisely monitored in this position.…”
Section: Mechanical and Volumetric Change Detectionmentioning
confidence: 99%
“…Another work with FBGs measured the refractive index of the electrolyte as a result of the changes in conductive ion concentration [ 127 ]. Illustrated in Figure 9 , Nedjalkov et al introduced a novel fiber design: in addition to FBGs in the fiber core, an additional optical waveguide was inscribed within the cladding of the original fiber using the point-by-point method via a femtosecond laser to enhance its sensitivity to refractive index variation in battery ionic solutions.…”
Section: Parameter Monitoring For General Operation Of Batteriesmentioning
confidence: 99%
“… Schematics of typical and sensitivity-enhancing optical waveguide structure [ 127 ]: ( a ) the original design where gratings are inscribed into the fiber core; ( b ) the self-compensating design that can enhance refractive index sensitivity by inscribing an additional waveguide in the cladding to divert a portion of the propagating light. …”
Section: Figurementioning
confidence: 99%
“…Second, changes in Li + solvation will likely increase the refractive index of the electrolyte by typically 0.1% per Li + molar concentration, as was demonstrated with different salts and salt concentations. 67,68 This changes the interference conditions in the fibre and may affect the amount of Raman pump light propagating along the hollow-core fibre. 39 PVDF binder, and 5 wt.% Timcal C45 conductive carbon on 20 um thick aluminium foil.…”
Section: Ec-raman Bandmentioning
confidence: 99%